Determinants of maternity services utilisation among women of reproductive age across sub-Saharan Africa - Julia Marie Hajjar; Obasanjo Bolarinwa; Oluwatobi Abel Alawode; Adeolu Anthony Olagunju; Lawrence Jones-Esan; Sanni Yaya (PLoS ONE, 2026)
Background In 2020, approximately 800 women died daily as a result of largely preventable complications of pregnancy and delivery globally. Almost 95% of these deaths occurred in low- and middle-income countries. Even though antenatal care, institutional delivery, and postnatal care constitute lifesaving maternal and newborn healthcare services, uptake is variable between countries in sub-Saharan Africa. Thus, this study examined the coverage and factors influencing the utilisation of maternal and newborn health services in sub-Saharan Africa. Methods This current study pooled datasets from the Demographic Health Surveys conducted in 27 countries in sub-Saharan Africa between the years 2010–2020. The outcome variables were maternal and newborn health services measured by antenatal care visits, institutional delivery, and postnatal care visits among 58,648 women of reproductive age between the ages of 15–49. Multilevel analysis was employed to examine the associated factors at a p < 0.05 level of significance. Results The overall analysis of the prevalence of maternal and newborn health services among women of reproductive age in sub-Saharan Africa was 67.3%, 74.5%, and 32.5% for 4 + antenatal care visits, institutional delivery and visits to postnatal care within 48 hours of delivery, respectively. Antenatal care visits were highest in Sierra Leone at 91.4%, and Institutional delivery was highest in Gabon at 97.6%, whilst Niger had the lowest prevalence for antenatal care visits and institutional delivery at 38.0% and 42.3%, respectively. Cote d’Ivoire reported the highest prevalence of postnatal care with 78.8%, whilst Malawi reported the lowest with 7.3%. Moreover, women with secondary/higher education were more likely to utilise antenatal care (aOR=2.09; 95% CI:1.96–2.23) and have institutional delivery (aOR=2.54; 95% CI:2.34–2.74) compared to those with no education. Furthermore, being employed was associated with a higher likelihood of utilising postnatal care (aOR=1.28; 95% CI:1.22–1.34) within 48 hours of delivery compared to women without formal employment. Conclusion The study concluded that women of reproductive age in sub-Saharan Africa who were educated were more likely to seek antenatal care and have institutional delivery, whilst women who were employed were more likely to utilise postnatal care within 48 hours of delivery. Therefore, future initiatives should focus on empowering and strengthening the education of girls and women in sub-Saharan Africa.